Do The Facts of Voting Rights Support Chief Justice Roberts’s Opinion in Shelby County? - Morgan Kousser (Transatlantica)
In June, 2013, a 5-4 majority of the U.S. Supreme Court brought to an abrupt and likely permanent end the most important provision of the most successful civil rights law in U.S. history. Initially passed in 1965, Section 5 of the Voting Rights Act required “covered jurisdictions,” at first in the Deep South and later extended to Texas, Arizona, Alaska, and certain counties and townships in other states, to “pre-clear” any changes in their election laws with the Justice Department or the District Court of the District of Columbia before putting them into effect. Laws that changed the political structure – for instance, redistricting laws, annexations, and shifts from district to “at-large” elections for local governments – were restricted, as well as provisions and practices that directly affected individuals’ rights to vote. While acknowledging the success of the law in greatly increasing the number of African-American and Latino elected officials, Chief Justice John Roberts contended in his majority opinion in Shelby County v. Holder that the problems of 2013 were much less grave than the “pervasive . . . flagrant . . . widespread . . . rampant” voting discrimination of 1965 and that the coverage formula was outmoded because “today’s statistics tell an entirely different story.”1Neither the Chief Justice nor any scholars or civil rights proponents or opponents have systematically examined the evidence on the entire pattern of proven voting rights violations over time and space. Was the Chief Justice correct in asserting that such violations no longer tracked the coverage scheme in Section 4 of the Act -- that, as he put it, the relationship of the formula to problems of vote dilution was purely “fortuitous?” Had the number of violations diminished so much in the years leading up to the 2006 renewal of Section 5 that Congress should have ended preclearance altogether because discrimination had basically disappeared? If the number of voting rights lawsuits has diminished, why is that so?Based on the largest database of voting rights “events” – successful lawsuits, Section 5 Justice Department objections and “more information requests,” and consent decrees or settlements out of court that led to pro-minority changes – ever compiled, this paper provides a unique overview of the history of U.S. voting rights from 1957, when the first U.S. civil rights law in 82 years passed, through 2013. It shows that the Chief Justice’s factual assertions were incorrect, that the coverage formula was still congruent with proven violations, and that to the extent that recorded violations had decreased, that was not because problems had ended, but because the Supreme Court had made it more difficult to win lawsuits.